NUS 2013: Book of Abstracts: 3rd International Conference on Neglected and Underutilized Species: for a Food-Secure Africa, Accra, Ghana, 25-27 September 2013 - Hall, R.A.; Rudebjer, P.G.; Padulosi, S.; Bioversity International (2013)
The book comprises all the abstracts presented either orally or as posters at the conference. The large number of abstracts received (438) reflects a growing interest in the use enhancement of underutilized crops. The message that the world is over-dependent on a small number of varieties of just a few crops (rice, maize, wheat and potato) is getting across, especially in Africa.